Comparative Genome Analysis of the Lignocellulose Degrading Bacteria Citrobacter freundii so4 and Sphingobacterium multivorum w15 - Cortes-Tolalpa, Larisa; Wang, Yanfang; Salles, Joana Falcao; van Elsas, Jan Dirk (Frontiers in Microbiology, 2020)
Two bacterial strains, denoted so4 and w15, isolated from wheat straw (WS) degrading microbial consortia, were found to grow synergistically in media containing WS as single carbon and energy source. They were identified as Citrobacter freundii so4 and Sphingobacterium multivorum w15 based on 16S rRNA gene sequencing and comparison to the respective C. freundii and S. multivorum type strains. In order to identify the mechanisms driving the synergistic interactions, we analysed the draft genome of two strains and further characterized their metabolic potential. The latter analyses revealed that the strains had largely complementary substrate utilization patterns, with only 22 out of 190 compounds shared. The analyses indicated C. freundii so4 to primarily consume amino acids and simple sugars, with laminarin as a key exception. In contrast, S. multivorum w15 showed ample capacities to transform complex polysaccharides, including intermediates of starch degradation. Sequence analyses revealed C. freundii so4 to have a genome of 4,883,214 bp, with a G+C content of 52.5%, 4,554 protein-encoding genes and 86 RNA genes. S. multivorum w15 has a genome of 6,678,278 bp, with a G+C content of 39.7%, 5,999 protein-encoding genes and 76 RNA genes. Genes for motility apparatuses (flagella, chemotaxis) were present in the genome of C. freundii so4, but absent from that of S. multivorum w15. In the genome of S. multivorum w15, 348 genes had regions matching CAZy family enzymes and/or carbohydrate-binding modules (CBMs), with 193 glycosyl hydrolase (GH) and 50 CBM domains. Remarkably, 22 domains were predicted to encode proteins matching enzymes of glycoside hydrolase family GH43, suggesting a strong investment in the degradation of arabinoxylan. In contrast, 130 CAZy family genes were found in C. freundii so4, with 61 GH and 12 CBM domains identified. Collectively, our results based on both metabolic potential and genome analyses revealed the two strains to harbour complementary catabolic armouries, with S. multivorum w15 primarily attacking the WS hemicellulose and C. freundii so4 the cellulose, next to emerging oligo- or monosaccharides. Finally, C. freundii so4 may secrete secondary metabolites that S. multivorum w15 can consume, and detoxify the system by reducing the levels of (toxic) by-products.